2011
DOI: 10.1002/cne.22701
|View full text |Cite
|
Sign up to set email alerts
|

Blueprint of an ancestral neurosensory organ revealed in glial networks in human dental pulp

Abstract: Sensory function of human dental pulp has long been known. A composite role has been suggested for odontoblasts as sensory cells in addition to the synthesis of dentinal matrix. However, the neural basis for such a composite sensory activity remains enigmatic. Here, we aimed to probe the question by pursuing an evolutionary logic; if dental pulp is a vestigial sensory organ co-opted to a function of synthesis of mineralized matrix, essential elements of neurosensory organs may persist in dental pulp. Through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 125 publications
3
43
0
Order By: Relevance
“…The term telacyte (Latin tela = web) was proposed by us for these cells. Telacytes were characterized as astrocyte-like glia by low-level expression of GFAP where the product was not detected immunohistochemically but showed high expression of S100B mRNA in accord with immunologically detected expression of this protein [Farahani et al, 2011]. These cells also expressed genes encoding vascular endothelial growth factor (VEGF) [Virtej et al, 2013], nerve growth factor (NGF) and low-affinity nerve growth factor receptor (P 75 NTR) [Woodnutt et al, 2000].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…The term telacyte (Latin tela = web) was proposed by us for these cells. Telacytes were characterized as astrocyte-like glia by low-level expression of GFAP where the product was not detected immunohistochemically but showed high expression of S100B mRNA in accord with immunologically detected expression of this protein [Farahani et al, 2011]. These cells also expressed genes encoding vascular endothelial growth factor (VEGF) [Virtej et al, 2013], nerve growth factor (NGF) and low-affinity nerve growth factor receptor (P 75 NTR) [Woodnutt et al, 2000].…”
Section: Discussionmentioning
confidence: 84%
“…Cells intensely reactive with anti-GFAP antibody, and previously termed seracytes by us, were characterized as phenotypically similar to radial glial cells of the central nervous system [Farahani et al, 2011]. Inter-odontoblastic seracytes are distinct in anatomical location and gene expression profile from postnatal stem cells isolated from the central region of dental pulp [Gronthos et al, 2000;Miura et al, 2003], and are also distinct from dental pulp stromal cells derived from dental pulp mesenchymal stem cells [Marchionni et al, 2009;Pivoriuūnas et al, 2010].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teeth provide a uniquely discriminating sense of touch and directional specificity for occlusal awareness, intra-oral contact for management of a food bolus, discrimination of food texture and hardness, and control of jaw muscles for mastication and swallowing (Klineberg et al 2012). These specific features of teeth are closely linked with the periodontal sensitivity, suggesting an integrated role of the pulp-dentine-enamel complex (Farahani et al 2011). Many studies have shown that poor mastication due to tooth loss, acting as stress, causes various reactions of the autonomic nervous system and endocrine system, activates the hypothalamic-pituitary-adrenal (HPA) axis and transmits to the hypothalamus to increase the release of corticotrophin-releasing hormone (CRH), inducing the secretion of adrenocorticotropic hormone (ACTH) from the anterior pituitary, which stimulates the adrenal cortex to produce glucocorticoids, such as cortisol in humans and corticosterone in mice (Levine 2005).…”
Section: Introductionmentioning
confidence: 99%